2020
DOI: 10.1259/bjr.20190464
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing oropharyngeal cancer survival outcomes: a decision tree approach

Abstract: Objectives: To analyze survival outcomes in patients with oropharygeal cancer treated with primary intensity modulated radiotherapy (IMRT) using decision tree algorithms. Methods: A total of 273 patients with newly diagnosed oropharyngeal cancer were identified between March 2010 and December 2016. The data set contained nine predictor variables and a dependent variable (overall survival (OS) status). The open-source R software was used. Survival outcomes were estimated by Kaplan–Meier method. Important explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Despite these potential concerns, in this analysis, we found that NRG Oncology nomograms for predicting PFS and OS performed well on a large, population‐based data set with higher rates of comorbidities and treatment variation than the data sets used to create them. Numerous models have been developed to account for the array of potentially relevant risk factors, to predict outcomes for patients with OPSCC (and non‐OPSCC) 1,2,3,4,5,7,8,9,20 . Generally, the objectives of creating such models are: 1) to give patients, providers, and researchers reliable estimates of long‐term outcome probabilities associated with a particular individual's (or set of individuals') disease and its treatment, and 2) to define risk strata for the purposes of guiding appropriate treatment for these individuals, particularly with respect to treatment (de)intensification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these potential concerns, in this analysis, we found that NRG Oncology nomograms for predicting PFS and OS performed well on a large, population‐based data set with higher rates of comorbidities and treatment variation than the data sets used to create them. Numerous models have been developed to account for the array of potentially relevant risk factors, to predict outcomes for patients with OPSCC (and non‐OPSCC) 1,2,3,4,5,7,8,9,20 . Generally, the objectives of creating such models are: 1) to give patients, providers, and researchers reliable estimates of long‐term outcome probabilities associated with a particular individual's (or set of individuals') disease and its treatment, and 2) to define risk strata for the purposes of guiding appropriate treatment for these individuals, particularly with respect to treatment (de)intensification.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Various risk modeling approaches have been used to determine the relative prognostic value of risk factors, including recursive partitioning analysis (RPA), random forests, machine learning, and risk scores based on multivariable regression. 1,2,5,7,8,9 The latter approach in particular lends itself to the generation of nomograms and other graphical tools that can map a large set (vector) of risk factors to a single (scalar) estimate, such as the probability of overall survival (OS) at 5 years. Such estimates may be useful in aiding provider-patient discussions and defining eligibility for clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After then, the “rpart” Package ( ) was used to construct decision tree and split patients as different from each other as possible. It was implemented to decide which of these variables to split and the splitting value in each step of the tree’s construction ( 43 ). Moreover, a nomogram model, which is an individualized risk prediction model to predict the 1, 3, 5-year survival probability, was constructed using the “RMS” package.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 12 of the included studies considered oncological outcomes following curative-intent treatment as their target of prediction. In details, six studies (40,42,(78)(79)(80)(81) aimed at predicting OS, while five (40, 82-85) considered loco-regional control (LRC) and one (86) distant metastasis-free survival (DMFS). Only two works focused on more than one oncological outcomes (40,87).…”
Section: Oncological Outcome Predictionmentioning
confidence: 99%